Analysis of Guarantee’s Rights in Marriage by Perspective of Womens’s Study Center of Sunan Kalijaga UIN: A gander Perspective Study - Abdilah, Nadhruna'im (Faculty of Shariah UIN Ponorogo, 2023)
Based on the changing meaning of ijbar, which the majority of Indonesians equate with ikrah, especially from the gender perspective of the Women's Study Center at UIN Sunan Kalijaga, researchers are encouraged to do the following research . From the perspective of gender institutions, what is the development of the implementation of Ijbar rights in Indonesia today? Equality, UIN Sunan Kalijaga Women's Studies Center? (3) Women's human rights degraded as a result of forced marriage as a result of the use of ijbar in marriage, based on the perspective of UIN Sunan Kalijaga's Center for Women's Studies What are the legal protections for the research? As a research type, we have adopted a field research with a statutory formal approach. The data analysis method uses descriptive analysis in multiple stages such as pre-study, data processing, data validity check and data analysis. All data were obtained by observation and interview methods. The research showed that after the enactment of the Marriage Law and the compilation of Islamic law, absolute rights to izibals became unenforceable in Indonesia. Many articles indicate that permission for newlyweds or would-be couples is an important part of the wedding ceremony itself. According to UIN Sunan Kalijaga's Center for Women's Studies, Ijbar's conception of her Fiqh There are legal grounds. The basis is in the hadiths of the Prophet found in various hadith books. As one of the concepts forming the legal basis of fiqh in relation to the rule of law, fiqh experts hold mixed opinions on forced marriage (ijbar). The Women's Studies Center at UIN Sunan Kalijaga offers her two types of legal protection in terms of Islamic law to women whose human rights have been violated as a result of marriage to Ijbar rights. First, all women have an equal right to choose a partner. Second, women may be asked by their guardians permission to marry without their knowledge or consent.